Fraud responses through short text messages (SMS): A qualitative study on enthusiasm, power of influences and impacts to the university students / Mohamad Ridhuan Mat Dangi and Norulhuda Tajuddin - Mat Dangi, Mohamad Ridhuan; Tajuddin, Norulhuda (2013)
The rapid growth of technology especially in the telecommunication field today brings the pro and contra upon its implementation. The digital waves have transformed the communication process among people around the world The Short Text Message Service or SMS for short is one of the features contained in the mobile phone that is popularly used by the users. Despite being meaningful to ease users communicating with others remotely and globally, it also brings together the chances and opportunities for the criminal actions. Among the well-known criminal activities related to the use of SMS is the fraud SMS; operating in different types of conduct. The fraud activities also evolve from time to time in line with the development of technologies that allows the fraudster to creatively manipulate the SMS services as a trap to the victims. Therefore, this study is conducted with the objectives to discover factors which motivate an individual to respond to fraud SMS. to identify the reasons why victims are susceptible to fraud SMS, to recognize the impacts received by individuals who are victims of fraud SMS and to identify and determine the appropriate measures to avoid and prevent the problem of fraud SMS. This study revealed that. one can receive 1 to 5 fraud SMSes since they have started using mobile phones. A majority of the respondents are aware of the fraud SMS and agree that it is a form of cheating through mobile technology. The individual's attitude. behavior and financial problems are among the reasons why the victims response to fraud SMS.